BEHIND THE SCENES OF ANONYMOUS: POWER MECHANISMS AND ONLINE PROSTITUTION PRACTICES ON MICHAT - Fatimah, Syarifah; Ronda, Mirza; Napitupulu, Frengki (International Journal of Social Science, 2025)
The development of digital technology has created new interaction spaces that enable online prostitution, one of which is through the MiChat application. The anonymity and people nearby features make it easier for users to interact without clear identities, creating a loophole for covert sexual transactions. This research uses a critical paradigm with a qualitative approach through interviews, digital observation, and document analysis to understand how anonymity operates as a mechanism of power. The results show that coded language such as "ST/LT," "Open BO," and "300 up" are used to disguise transactions, while the application's algorithm reinforces power relations through account visibility. Social factors such as economic pressure, a consumptive lifestyle, and low digital literacy contribute to increasing adolescent vulnerability. In conclusion, online prostitution on the MiChat application is not only the result of individual abuse, but also the result of the interaction between technological design, anonymity, and social structures that support exploitative practices in the digital space